Interaction Use Paylater Regarding Student Decisions with Lifestyle as Variables Moderation in the Perspective of Islamic Economics : A Case Study of FEBI Students at UIN North Sumatra - Iqbal, Muhammad; Syahbudi, Muhammad; Rahmani, Nur Ahmadi Bi (Journal of Applied Business Administration, 2025)
The advancement of financial technology has given rise to Paylater services, which are increasingly favored by university students, particularly for fulfilling their consumption needs directly. However, this convenience has the potential to trigger consumer behavior that conflicts with it. Based on this phenomenon, this study formulates the following question: Does the use of a Paylater perspective influence students' consumption decisions, and does lifestyle moderate this relationship? This study aims to analyze the effect of Paylater usage on student decisions and to examine the role of lifestyle as a moderating variable. The method employed is a quantitative approach using multiple regression and Moderated Regression Analysis (MRA). A sample of 98 students from the Faculty of Islamic Economics and Business at UIN North Sumatra was obtained through purposive sampling. The results indicate that Paylater usage has a significant effect on students' consumption decisions. Furthermore, lifestyle is proven to moderate this relationship, where a consumptive lifestyle strengthens the influence of pay later on consumption decisions. These findings indicate a shift in student consumption patterns toward instant and emotional behavior. Therefore, financial literacy education based on Sharia principles and promotion is necessary to address the penetration of digital financial services.